Analytical study of the Middle Kingdom group of gold jewellery from tomb 124 at Riqqa, Egypt. (18th March 2019) - Troalen, Lore; Guerra, Maria F.; Maitland, Margaret; Ponting, Matthew; Price, Campbell
Abstract : The jewellery from tomb 124 at Riqqa, consisting of one pectoral and one winged beetle in gold and cloisonné work, one gold shell pendant decorated with wires and granulation, and one hollow gold amulet in the form of god Min, was analysed by handheld X‐ray fluorescence and scanning electron microscopy with energy‐dispersive X‐ray spectroscopy. This group of jewellery, dated to the second half of the 12th Dynasty (c. 1900–1840 B.C.), was excavated inside the coffin of an adult male, which had been crushed after burial by the collapse of the chamber roof during an episode of looting. Both the male and the looter's body were found inside the chamber, evidencing that the group of jewellery was intact. Despite having been highly restored in the past, as referenced in the correspondence between the excavator Flinders Petrie and the curators of the Manchester Museum, it could be shown that the jewellery was produced using Ag‐rich electrum alloys containing platinum group element inclusions that indicate the use of alluvial gold. The analysis of some joins has confirmed the use of hard‐soldering, with solders obtained by addition of Cu to the base‐alloy. Data obtained for the jewellery of tomb 124 were compared with data previously obtained for tomb 296, also excavated at Riqqa, but dated to the 18th Dynasty. The comparison demonstrates the continuity of the workshop traditions in one location between the Middle Kingdom and the New Kingdom but also reveals discrepancies in the alloys employed in those two periods.